Video-based training to improve perceptual-cognitive decision-making performance of Australian football umpires - Larkin, P.; Mesagno, C.; Berry, J.; Spittle, M.; Harvey, J. (Journal of Sports Sciences, 2018)
Decision-making is a central component of the in-game performance of Australian football umpires; however, current umpire training focuses largely on physiological development with decision-making skills development conducted via explicit lecture-style meetings with limited practice devoted to making actual decisions. Therefore, this study investigated the efficacy of a video-based training programme, aimed to provide a greater amount of contextualised visual experiences without explicit instruction, to improve decision-making skills of umpires. Australian football umpires (n = 52) were recruited from metropolitan and regional Division 1 competitions. Participants were randomly assigned to an intervention or control group and classified according to previous umpire game experience (i.e., experienced; less experienced). The intervention group completed a 12-week video-based decision-making training programme, with decision-making performance assessed at pre-training, and 1-week retention and 3-week retention periods. The control group did not complete any video-based training. Results indicated a significant Group (intervention; Control) × Test interaction (F(1, 100) = 3.98; P = 0.02, partial ?2 = 0.074), with follow-up pairwise comparisons indicating significant within-group differences over time for the intervention group. In addition, decision-making performance of the less experienced umpires in the intervention group significantly improved (F(2, 40) = 5.03, P = 0.01, partial ny2 = 0.201). Thus, video-based training programmes may be a viable adjunct to current training programmes to hasten decision-making development, especially for less experienced umpires.